Charles Bridgeman (C. 1685-1738) A Landscape Architect of the Eighteenth Century. - Haynes, Susan (Garden and landscape history., 2023)
An examination of the garden plans of eighteenth-century landscape architect Charles Bridgeman, shedding light on his artistic vision and contributions to English garden history.